0162 Developing A Mobile App To Improve Access And Application Of Key Hospital Guidelines. (1st November 2014) - Kwa, Adrian; Wilson, Tony; Carter, Mark; Page, Duane; Brown, Michael; Bennett, Owen; Miles, Giulia; Baxendale, Bryn
Abstract : Background: The "August effect" is a well described phenomenon that occurs annually when final year medical students commence their first postgraduate job 1 with some data suggesting around six times more in-hospital deaths in August than would be expected from the volume and case-mix of admissions. 2 Observation of junior doctors' performance on night shifts suggests that inexperience, unfamiliarity with local policies and guidelines, and failure to recognise and escalate care appropriately are important factors. Timely access to accurate contextual safety critical information is proposed as an aid to improve performance of new graduate doctors. Numerous website and clinical apps of varying quality exist but may contain inaccurate information concerning some clinical conditions (eg Wikipedia). 4 Information contained may also differ from how it is presented in local Trust guidelines. Methodology: Using a user-centred design approach, we developed an application for mobile devices which aimed to contain all Trust-approved clinical guidelines. We ran focus group meetings and performed critical incident techniques and card sorting exercises. We then produced a prototype and performed field testing, where users were asked to find a number of guidelines without the use of search function. The prototype was rated using System Usability Score. Outcomes: A 'System Usability Score' of 83 was achieved during the design phase, suggesting junior clinicians will be able to manoeuvre through the App effectively to locate key information. The next phase of 'beta-testing' in clinical practice (with more experienced clinicians) and simulated settings (with undergraduates and junior clinicians) will evaluate 'live use' of the App, focusing on functionality and any glitches. Potential impact: A well-designed App providing timely and easy access to approved guidelines and related operational information will help improve reliability of patient care and enhance learning in practice. This has the potential to impove patient safety and reduction in morbidity and mortality. References: Vaughan L, McAlister G, Bell D. Clinical Medicine 2011;11:322–6 Dr Foster. My Hospital Guide 2012 (as of 1st June 2013) Blakey JD, Fearn A, Shaw DE. Journal of Royal Society of Medicine Short Reports 2013; 4:1–7 Hasty RT, Garbalosa RC, Barbato VA et al . J Am Osteopath Assoc 2014;114(5): 368–373